PENERIMAAN PANELIS DAN SIFAT KIMIAWI EMULSI LABU KUNING DAN FRAKSI OLEIN SAWIT - Anton Rahmadi; Yuliadini Puspita; Sukmiyati Agustin; Miftakhur Rohmah (Jurnal Teknologi dan Industri Pangan, 2015)
This study aimed to produce functional food products with the main ingredient of pumpkin and olein fraction of red palm oil (OF-RPO). This research was conducted in two stages. The first was to analyze consumer acceptance where a Completely Randomized Design was used with one factor. The factor was the composition of pumpkin and OF-RPO levelled as follow: 100:0, 95:5, 90:10, 85:15, 80:20, and 0:100 (v/v). In the second stage, analyses of carotenoids using HPLC, FFA, pH, vitamin C, and peroxide values were carried out on selected formula (mixture of pumpkin and OF-RPO), formula with 100 mL of pumpkin, formula with 100 mL of OF-RPO, and negative control (without pumpkin and OF-RPO), before and after the storage period of two months, except for HPLC analysis. The best formula based on acceptance test was a composition of 90 mL pumpkin and 10 mL OF-RPO was further diluted 1:4 (v/v). Characteristics of the product were sweet, sour, not bitter, not grassy, and not rancid. The emulsion product contains trans-β-carotene at 141.65±0.47 mg/L, equivalent to 237 UI activity of vitamin A/mL. The content of trans-β-carotene was found at the highest (341.83 mg/L) from the pumpkin juice, while the OF-RPO had the lowest trans-β-carotene content (41.2 mg/L). Product was acidic with a pH of 3.6±0.1 and with vitamin C content of 13.2±1.2 mg/100 g of product. Acidity and vitamin C levels tended to remain stable during the storage period for two months. Peroxide value of the emulsion product was at 0.8 mEq oxygen/kg. The FFAs were in the range of 1.59 to 1.73% and they also did not change significantly after storage for two months.